Zero Trust Architecture in Corporate Cybersecurity Systems - Moskvin, K.; Sievierinov, O. (ХНУРЕ, 2025)
The Zero Trust architecture is described as a modern approach to cybersecurity based on the principle of a complete lack of trust in any network elements. The main principles of Zero Trust and implementation stages are considered. The advantages of Zero Trust for corporate systems, such as increased security, flexibility, compliance with regulatory requirements, and reduced attacks, are identified. The problems of implementation are considered and recommendations for the successful integration of Zero Trust in organizations are given.
Keywords: ero Trust Architecture; Continuous Verification; Multi-Factor Authentication (MFA); Micro- Segmentation; Insider Threats; Modern Cyber Threats